Estudio preliminar del crecimiento del alcornoque en la fase juvenil. - Oliva, M; Molinas, A Caritat M; Caritat, A; Molinas, M (SCIENTIA gerundensis, 1989)
Shoot elongation has been measured in two different groups of juvenil cork-oaks (Quercus suber) by means of their budding segments. One group has got 14 seedlings three years old, proceeding from a forest nursery. The other group consistes in 17 sprouts of three and one years old from a bumed cork-oak forest. Buddings segments of the three- years old seedlings show an average elongation of 4,l cm. Sprouts are more vigorous; the three years old ones have an average value of segment elongation of 6,05 cm, and the one year old ones an average value of 15,3 cm. A decrease in elongation appears along the succesive buddings
Keywords: buds; cork-oak; Quercus suber; shoot elongation; sprouts